2021
DOI: 10.1021/acs.inorgchem.1c00285
|View full text |Cite
|
Sign up to set email alerts
|

Unsupported Lanthanide–Transition Metal Bonds: Ionic vs Polar Covalent?

Abstract: Lanthanide−transition metal complexes continue to be of interest, not only because of their synthetic challenge but also of their promising magnetic properties. Computational work examining the chemical bonding between lanthanides and transition metals in PyCp 2 Ln-TMCp(CO) 2 (DyPyCp 2 2− = [2,6-(CH 2 C 5 H 3 ) 2 C 5 H 3 N] 2− ) reveals strong Ln−TM dative bonds. Gasphase optimized geometries are in good agreement with experimental structures at the density functional theory (DFT) level with large-core pseudop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…84,119,120 In 2021, Hall and fellows elucidated the nature of Ln–TM bonds in PyCp 2 Ln-TMCp(CO) 2 (PyCp 2 2− = [2,6-(CH 2 C 5 H 3 ) 2 C 5 H 3 N] 2− , TM = Fe, Ru) using multiple computational tools containing natural bond orbital (NBO) analysis, topological analysis, and energy decomposition analysis (EDA), showing that these special interactions were very similar to the Ln–I bonds and consist of predominant electrostatic contributions as well as significant orbital mixing and dispersion contributions. 121 On the other hand, concerning the vital role of Ln ions in SMMs field, inspecting the effects of Ln–TM bonds on the SMM behaviors is also an important line of inquiry. In 2018, Nippe et al reported the magnetization dynamics of the Ln–TM bonded compounds for the first time, PyCp 2 Dy–FeCp(CO) 2 and PyCp 2 Dy–RuCp(CO) 2 with Dy–Fe and Dy–Ru distances of 2.884(2) and 2.9508(5) Å, respectively (Fig.…”
Section: Magnetic Behaviour Under Metal–metal Bondsmentioning
confidence: 99%
“…84,119,120 In 2021, Hall and fellows elucidated the nature of Ln–TM bonds in PyCp 2 Ln-TMCp(CO) 2 (PyCp 2 2− = [2,6-(CH 2 C 5 H 3 ) 2 C 5 H 3 N] 2− , TM = Fe, Ru) using multiple computational tools containing natural bond orbital (NBO) analysis, topological analysis, and energy decomposition analysis (EDA), showing that these special interactions were very similar to the Ln–I bonds and consist of predominant electrostatic contributions as well as significant orbital mixing and dispersion contributions. 121 On the other hand, concerning the vital role of Ln ions in SMMs field, inspecting the effects of Ln–TM bonds on the SMM behaviors is also an important line of inquiry. In 2018, Nippe et al reported the magnetization dynamics of the Ln–TM bonded compounds for the first time, PyCp 2 Dy–FeCp(CO) 2 and PyCp 2 Dy–RuCp(CO) 2 with Dy–Fe and Dy–Ru distances of 2.884(2) and 2.9508(5) Å, respectively (Fig.…”
Section: Magnetic Behaviour Under Metal–metal Bondsmentioning
confidence: 99%
“…When the fragments are computed as neutral species, the orbital interactions play the dominant role in the overall bonding energy -they constitute 66% of the attractive interaction, compared to 31% when the fragments are computed as charged species. The EDA analyses carried out by the group of Hall in a recent study 34 resulted in comparable differences in the relative contribution of the attractive orbital energy, depending on the charge of the fragments. In this study, the authors marked the difference between a situation with 26% of orbital interaction, analyzed as predominantly electrostatic, and another with 35 % of orbital interaction, analyzed as predominantly covalent.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…29,33 As such, the use of this empirical metric as a guide for the bonding strength can be counterintuitive: reporting a short distance does not inform on the nature of the bonding, and the net definition of a lanthanide-transition metal bond can then be somewhat confusing in the literature. Based on these important remarks, Hall and co-workers recently studied a series of unsupported bimetallic complexes containing lanthanide and transition metal ions, 34 which were designed by the group of Nippe. 35 This study is an important addition to the discussion on the nature of metal-metal bonding and insists on the relative comparison along the series to validate the theoretical results.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have thus been devoted to the formation of various intermetallic interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Although highresolution X-ray diffraction analysis can provide insight into the electron density of bonds, 19 theoretical calculations are widely conducted for examining intermetallic interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In this study, we synthesized heterometallic Ln-Pt complexes:…”
Section: Introductionmentioning
confidence: 99%